Provider Experiences With the Identification, Management, and Treatment of Co-occurring Chronic Noncancer Pain and Substance Use in the Safety Net. (28th January 2017) - Chang, Jamie Suki; Kushel, Margot; Miaskowski, Christine; Ceasar, Rachel; Zamora, Kara; Hurstak, Emily; Knight, Kelly R.
ABSTRACT: Background : In the United States and internationally, providers have adopted guidelines on the management of prescription opioids for chronic noncancer pain (CNCP). For "high-risk" patients with co-occurring CNCP and a history of substance use, guidelines advise that providers monitor patients using urine toxicology screening tests, develop opioid management plans, and refer patients to substance use treatment. Objective : We report primary care provider experiences in the safety net interpreting and implementing prescription opioid guideline recommendations for patients with CNCP and substance use. Methods : We interviewed primary care providers who work in safety net settings ( N = 23) on their experiences managing CNCP and substance use. We analyzed interviews using a content analysis method. Results : Providers found management plans and urine toxicology screening tests useful for informing patients about clinic expectations of opioid therapy and substance use. However, they described that guideline-based clinic policies had unintended consequences, such as raising barriers to open, honest dialogue about substance use and treatment. While substance use treatment was recommended for "high-risk" patients, providers described lack of integration with and availability of substance use treatment programs. Conclusions : Our findings indicate that clinicians in the safety net found guideline-based clinic policies helpful. However, effective implementation was challenged by barriers to open dialogue about substance use and limited linkages with treatment programs. Further research is needed to examine how the context of safety net settings shapes the management and treatment of co-occurring CNCP and substance use.